PENGARUH MODIFIKASI PERMUKAAN PISTON (DOME) DENGAN BAHAN BAKAR ETHANOL TERHADAP TORSI DAN DAYA PADA MESIN 4 LANGKAH ASTRO 108CC - Bagas Alfath Dinyar; Fadelan Fadelan; Kuntang Winangun (Universitas Muhammadiyah Ponorogo, 2022)
Replacing a standard piston with a dome piston can make changes to the performance of a 4 stroke combustion engine, this is due to the change in the compression ratio being larger, thus requiring fuel that contains a high octane number in order to get maximum combustion results. In the process of researching the piston which was originally raw in a convex shape, which aims to increase the compression ratio, changes that occur in engine performance can be observed from the test data in the test dyno. The results of the discussion or test on the effect of ethanol-fueled piston dome surface reconstruction on the performance of a 108cc 4 stroke engine with a standard piston diameter of 50 mm flat surface and a dome piston with a diameter of 51.5 mm convex surface which produces a compression ratio of 16.855 / 1 with the use of fuel. ethhanol fuel, it can be concluded that the maximum performance of a 4 stroke combustion engine is obtained in an engine that uses a dome piston with a power gain of 8.8 HP, which is an increase of 27% from an engine that uses a standard piston, and a torque of 7.79 Nm, which is an increase of about 9% from a standard piston engine. standard piston engine.